2008
DOI: 10.1007/s10689-008-9215-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel MLH1 genomic rearrangement as the cause of HNPCC in a Tunisian family: evidence for a homologous Alu-mediated recombination

Abstract: High rates of early colorectal cancers are observed in Tunisia suggesting high genetic susceptibility. Nevertheless, up to now no molecular studies have been performed. Hereditary nonpolyposis colorectal cancer (HNPCC) is the most frequent cause of inherited colorectal cancer. It is caused by constitutional mutations in the DNA mismatch repair (MMR) genes. Here, we investigated a Tunisian family highly suspected of hereditary nonpolyposis colorectal cancer (HNPCC). Six patients were diagnosed with a colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Previous reports of LS genomic rearrangements have highlighted the role of Alu-mediated homologous recombination as a common cause for these mutations but not recombination involving T stretches. 14,[17][18][19][20] Also, Alu-mediated homologous recombination seems to be more involved in MSH2 genomic rearrangements, whereas MLH1 rearrangements may originate from alternative mechanisms. 20,21 This LS genetic alteration was found in the MLH1 gene, whereas genomic rearrangements in MMR genes have been found more frequently in MSH2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of LS genomic rearrangements have highlighted the role of Alu-mediated homologous recombination as a common cause for these mutations but not recombination involving T stretches. 14,[17][18][19][20] Also, Alu-mediated homologous recombination seems to be more involved in MSH2 genomic rearrangements, whereas MLH1 rearrangements may originate from alternative mechanisms. 20,21 This LS genetic alteration was found in the MLH1 gene, whereas genomic rearrangements in MMR genes have been found more frequently in MSH2.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic study on genomic rearrangement in Lynch Syndrome showed that MLH1 and MSH2 are the most frequently targeted MMR genes for this type of mutation [14]. Furthermore, molecular characterisation of the breakpoints involved in large rearrangements within MLH1 and MSH2 genes showed that the majority are caused by homologous recombination between Alu repeats [1517]. These mutations are not usually detected by conventional methods of mutation analysis, such as denaturing high-performance liquid chromatography (DHPLC) and direct DNA sequencing, but they are detectable by a simple and robust technique such as the Multiplex Ligation-Probe Dependent Amplification (MLPA) [18, 19] assay.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to driving genome evolution, ARMDs also contribute to human disease. ARMDs occurring within the germline have been observed in several inherited disorders including α-thalassaemia, familial hypercholesterolaemia, Lesch–Nyhan syndrome, and Tay–Sachs disease [42], and have been implicated in the inactivation of tumor suppressor genes in familial cancers including CDH1 in hereditary diffuse gastric cancer [43], MLH1 in hereditary nonpolyposis colorectal cancer [44], MEN1 in multiple endocrine neoplasia type 1 [45], and BRCA1 in hereditary breast and ovarian cancer [46]. Alternatively, ARMDs of tumor suppressor genes have also been observed to occur somatically in tumor tissues such as TMPRSS2/ERG in prostate cancer [47], CAD in hepatoma [48], and TSC2 in tuberous sclerosis [49].…”
Section: Discussionmentioning
confidence: 99%